Critical investigation on the effect of steel strength on fatigue crack growth retardation including a single tensile overload. (December 2019) - Gadallah, Ramy; Tsutsumi, Seiichiro
Highlights: Effect of steel strength on FCG retardation was investigated by means of FEM. A combination of fracture analysis and an elasto-plastic model was performed. Steel strength revealed a significant influence on the calculated FCG retardation. Steel strength has a clear effect on the induced plastic zone size and Δ K . Abstract: The effect of steel strength on fatigue crack growth (FCG) retardation was investigated considering the influence of a single tensile overload (OL) by means of FEM. A technique that combines a fracture mechanics approach and an elasto-plastic material model available in WARP3D, an open source code, was applied. The interaction integral method provided by WARP3D was used to calculate stress intensity factor solutions based on the local stress fields obtained by elasto-plastic analyses. Crack growth calculations were then performed using Δ K obtained by the numerical analyses. FCG material properties were proposed for the employed steels based on elasto-plastic analyses where the residual stress fields induced by local plasticity ahead of the crack tip was considered. Calculated fatigue lives under two different loading patterns were verified with experiments. The results revealed that steel strength has a significant influence on the size of the induced plastic zone, crack geometry and the behavior of Δ K in particular after the OL. In addition, it is found that steel strength has a pronounced effect on the induced local stress field ahead of the crack tip as well as it exhibits a considerable influence on FCG retardation due to the OL. It is also noticed that, after the OL, the higher the steel strength the smaller the size of the induced plastic zone ahead of the crack tip as well as the higher the produced Δ K . This leads to accelerate FCG rate and shorten the resulting FCG retardation in which it influences the component service life.